Is it possible to sort the disability of individuals with migraine based on the International Classification of Functioning, Disability and Health? — A Scoping Review - Feitosa, Hugo; Wanderley, Débora; Barros, Manuella Morais Monteiro Barbosa; Silva, Suellen Freitas da; Santos, Alyne Karine de Lima; Tenório, Angélica da Silva; Oliveira, Daniella Araújo de (Headache Medicine, 2021)
Purpose To identify the most frequent outcomes related to disability assessed in individuals with migraine and to correlate these findings with the categories of International Classification of Functioning, Disability and Health. Material and method This scoping review was developed based on studies with adult population (18-55 years) of both sexes and assessing the disability generated by migraine. We included studies in which patients had a diagnosis of migraine based on International Classification of Headache Disorders. Results 52 articles were found with 42 outcomes related to 17 categories of International Classification of Functioning, Disability and Health, including the four main components of the classification, with seven categories in "Body Functions", one in "Body Structures", four in “Activities and Participation” and five in "Environmental Factors". Conclusion The findings show that disabilities, activity limitation, or participation restriction generated by migraine can be classified by International Classification of Functioning, Disability and Health. The components "body functions", "environmental factors" and "activities and participation" were the most identified in the present study. Thus, this classification is important to classify the disability caused by migraine and to guide a rehabilitation more focused on the patient's real demands, as well as directing the research involving this population.